Accumulation of a repulsive axonal guidance molecule RGMa in amyloid plaques: a possible hallmark of regenerative failure in Alzheimer's disease brains. Issue 2 (25th January 2013) - Satoh, J.; Tabunoki, H.; Ishida, T.; Saito, Y.; Arima, K.
<x xml:space="preserve">Abstract</x> J. Satoh, H. Tabunoki, T. Ishida, Y. Saito and K. Arima (2013) Neuropathology and Applied Neurobiology39, 109–120 Accumulation of a repulsive axonal guidance molecule RGMa in amyloid plaques: a possible hallmark of regenerative failure in Alzheimer's disease brains Aims: RGMa is a repulsive guidance molecule that induces the collapse of axonal growth cones by interacting with the receptor neogenin in the central nervous system during development. It remains unknown whether RGMa plays a role in the neurodegenerative process of Alzheimer's disease (AD). We hypothesize that RGMa, if it is concentrated on amyloid plaques, might contribute to a regenerative failure of degenerating axons in AD brains. Methods: By immunohistochemistry, we studied RGMa and neogenin (NEO1) expression in the frontal cortex and the hippocampus of 6 AD and 12 control cases. The levels of RGMa expression were determined by qRT‐PCR and Western blot in cultured human astrocytes following exposure to cytokines and amyloid beta (Aβ) peptides. Results: In AD brains, an intense RGMa immunoreactivity was identified on amyloid plaques and in the glial scar. In the control brains, the glial scar and vascular foot processes of astrocytes expressed RGMa immunoreactivity, while oligodendrocytes and microglia were negative for RGMa. In AD brains, a small subset of amyloid plaques expressed a weak NEO1 immunoreactivity, while some reactive astrocytes in both AD and control brains showed an intense NEO1 immunoreactivity. In human astrocytes, transforming growth factor beta‐1 (TGFβ1), Aβ1–40 or Aβ1–42 markedly elevated the levels of RGMa, and TGFβ1 also increased its own levels. Coimmunoprecipitation analysis validated the molecular interaction between RGMa and the C‐terminal fragment β of amyloid beta precursor protein (APP). Furthermore, recombinant RGMa protein interacted with amyloid plaques in situ. Conclusions: RGMa, produced by TGFβ‐activated astrocytes and accumulated in amyloid plaques and the glial scar, could contribute to the regenerative failure of degenerating axons in AD brains.